ORGANOLOGI ALAT MUSIK TRADISIONAL GAMBANG PRODUKSI SALMAN AZIZ DI KECAMATAN BANGKINANG KABUPATEN KAMPAR PROVINSI RIAU - Sabri, Sabri; Habibullah, Reizki; Nurmalinda, Nurmalinda (Institut Seni Indonesia (ISI) Surakarta, 2021)
Gambang's existence which is getting dimmer, has made the writer call to make it writing in organology studies. As a native of the region, the author feels he has a responsibility in the life of Gambang art. This organological study aims to become a written document of the process of making xylophones; when people want to learn to make xylophones, they can see this article. Thus also reducing the fear of the threat of extinction of the xylophone. This paper uses a descriptive analysis method using qualitative data, namely research conducted by approaching the object under study. The result of this paper is the process of making Gambang from the beginning to the end